Greening airports advanced technology and operations - Janic, Milan (Green energy and technology, 2011)
Greening Airports considers the greening, i.e., more sustainable development, of the entire air transport system - airports, air traffic control, and airlines - that could be achieved by the development and implementation of advanced operations and technologies. A broad overview of the general concept is given at the start of Greening Airports, which then goes on to provide a system for monitoring and assessing the level of greening of both the air transport system and individual airports. These are followed by analysis and modelling of the potential effects of particular advanced operations and technologies on the greening of airports and their local airspace. These include: the development of a large airport into a multimodal transport node by connecting it to a high speed rail network; the use of operations supported by new and existing air traffic control technologies to increase landing capacity of existing runways; the use of liquid hydrogen as a commercial aviation fuel; and the improvement of airport ground accessibility by a light rail rapid transit system. Greening Airports is written for researchers, planners, operators and policy makers in air transport.